Status Kondisi Fisik dan Keterampilan Siswa yang Mengikuti Ekstrakurikuler Futsal SMK Negeri 1 Kaliwungu Tahun 2022 - MURSYIDA, WILDAN BAGUS; Aji Putra, Ranu Baskora (Indonesian Journal for Physical Education and Sport, 2023)
This research was conducted aiming to determine the status of the physical condition and skills of students participating in the futsal extracurricular at SMK Negeri 1 Kaliwungu in 2022 with the components measured in this study including agility, leg muscle strength, speed, eye-foot coordination, passing, shooting, control, and dribbling. The research method used in this study was descriptive quantitative with 15 students participating in extracurricular activities at SMK Negeri 1 Kaliwungu. The sampling technique for this study was a test method, measuring physical condition and skills using the illiois agility test instrument. Data analysis techniques using T-score and percentage descriptive statistical analysis.The results of this study indicate that the status of the physical condition and skills of students participating in the futsal extracurricular included 1 student (6.7%) in the very good category, 4 students (26.7%) in the good category, 5 students (33.3%) with enough category, 4 students (26.7%) in the less category, 1 student (6.7%) in the very less category. and basic skills 1 student (6.7%) in the very good category, 3 students (20%) in the good category, 5 students (33.3%) in the sufficient category, 6 students (40%) in the less category, 0 students (0%) in the very less category. So it can be concluded that the physical condition and skills of students participating in the futsal extracurricular at SMK Negeri 1 Kaliwungu are in the "enough and insufficient" category.